ACUTE ABDOMEN IN CHILDREN - Irsal Munandar; Jon Hadi (Journal of Public Health Indonesian, 2025)
This article aims to provide a comprehensive understanding of the etiology, clinical manifestations, diagnostic process, and management of acute abdomen in children. The article is compiled using a descriptive narrative approach based on literature review from relevant medical journals and reference books. The review covers aspects of abdominal anatomy, pain classification, surgical and non-surgical etiologies, and diagnostic and therapeutic approaches. Acute abdomen in children has a wide variety of etiologies, including inflammation, obstruction, trauma, vascular disorders, and congenital disorders. The main manifestation is abdominal pain that can be divided into visceral, somatic, and referred pain, with various characteristics such as colicky, ischemic, and projected pain. The diagnostic process involves a thorough history taking, a systematic physical examination (inspection, palpation, percussion, auscultation), and supporting examinations such as laboratory, radiology, ultrasound, and CT scan. Management measures include emergency treatment, hemodynamic stabilization, and surgery if necessary. Acute abdomen is not a final diagnosis, but rather a collection of symptoms from various pathological conditions that require rapid evaluation. Therefore, appropriate management and early referral to a surgical specialist are crucial in reducing the risk of complications in pediatric patients. Rapid, accurate, and multidisciplinary management is key to improving the prognosis and survival of pediatric patients with acute abdominal symptoms.